Prevalence of common adverse events experienced following COVID‐19 vaccination and its associated factors in Ghana: Cross‐sectional study design. Issue 1 (24th December 2022) - Boi‐Dsane, Naa A. A.; Dzudzor, Bartholomew; Alhassan, Yakubu; Aheto, Justice M. K.
Abstract: Background and Aims: The novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) (COVID‐19) pandemic devasted the general life of people and various human activities across the globe, and Ghana is of no exception. This led to development of vaccines within record time to combat morbidity and mortality associated with the virus. In Ghana, COVID‐19 vaccines were introduced in addition to existing COVID‐19 protocols. However, the vaccines have adverse events among those who received them. In this study, we determined the prevalence of some common adverse events of the COVID‐19 vaccines and its associated sociodemographic factors in Ghana. Methods: An online snowball cross‐sectional survey was conducted between April and June 2021 among 240 people who had taken at least one dose of any of the COVID‐19 vaccines approved in Ghana. The penalized binary logistic regression model was used to assess the factors associated with experience of at least one adverse event and the experience of number of adverse events using Stata version 16. Results: Among the 240 participants, 88.2% had experienced at least one adverse event. The most common adverse event after the first dose was pain at injection site (65.8%), headache (57.5%), tiredness (55.8%), fever (51.7%), chills (39.6%), and muscle pains (38.3%). Experience of adverse events was 16 times higher among those who took their vaccines in Ghana (adjusted odd ratio [AOR]: 16.2, 95% confidence interval [CI]: 1.98–132.56, p = 0.009), 94% less among those who took AstraZeneca (India) compared to AstraZeneca (Oxford) (AOR: 0.06, 95% CI: 0.01–0.37, p = 0.002) and 86% less among 40–49 years compared with less than 30 years old (AOR: 0.14, 95% CI: 0.03–0.58, p = 0.007). Conclusion: Pain at the injection site, headache, tiredness, fever, chills, and muscle pains were the most frequently reported adverse events. The study identified country of vaccination, country of origin of AstraZeneca vaccine and age to be associated with adverse events of vaccination.